A note on Dolby and Gull on radar time and the twin 'paradox' - Eagle, A (American Association of Physics Teachers, 2005)
Recently a suggestion has been made that standard textbook representations of hypersurfaces of simultaneity for the travelling twin in the twin 'paradox' are incorrect. This suggestion is false: the standard textbooks are in agreement with a proper understanding of the relativity of simultaneity.